Tyrosinase-Based Reporter Gene for Photoacoustic Imaging of MicroRNA-9 Regulated by DNA Methylation in Living Subjects - Zheng, Haifeng; Zhou, Lin; Shi, Yaru; Tian, Jie; Wang, Fu (Molecular therapy. Nucleic acids, 2018)
MicroRNAs (miRNAs) are a class of negative regulators of gene expression and play critical roles in various biological processes. Conventional approaches for detecting miRNAs, such as northern blotting, microarray, and real-time PCR, usually require the lysis of cell samples and could not provide the in vivo information about miRNAs in living organisms. Here, we designed a tyrosinase (TYR)-based reporter to monitor miR-9 expression that is regulated by DNA methylation in living cells and animals. During DNA methylation of A549 cells treated by 5-aza-2′-deoxycytidine (5-Aza-dC), the CMV/TYR-3xTS reporter-transfected cells demonstrated a gradual decrease in melanin content, TYR activity, and photoacoustic signal because of the gradual activation of miR-9 expression. The miR-9-regulated repression of TYR activity also resulted in a significant decrease in photoacoustic signal from the flank of mice with 5-Aza-dC treatment, whereas the bioluminescence signal from internal control had no obvious change. The TYR-based miRNA reporter may serve as a new imaging probe for monitoring the dynamic expression of miRNAs during various cellular or disease progression in cells and living animals.